2012
DOI: 10.4269/ajtmh.2012.11-0534
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania chagasi in Opossums (Didelphis albiventris) in an Urban Area Endemic for Visceral Leishmaniasis, Campo Grande, Mato Grosso do Sul, Brazil

Abstract: We investigated the occurrence of Leishmania infantum chagasi in Didelphis albiventris opossums at a wild animal rehabilitation center in the city of Campo Grande, Brazil. A total of 54 opossums were tested for L. i. chagasi infection in peripheral blood and bone marrow samples. The samples were analyzed by direct examination, culturing in a specific medium, and polymerase chain reaction–restriction fragment length polymorphism. Leishmania i. chagasi DNA was detected by polymerase chain reaction–restriction fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
(23 reference statements)
2
20
0
4
Order By: Relevance
“…Cats and a different species of opossum ( M. domestica ) did not support sand fly development at all, and dogs were intermediate in their abilities to efficiently support the sand fly life cycle. These observations raise hypotheses about animals that could serve as potential reservoir hosts for Leishmania species (Humberg et al 2012). Recent studies have found evidence of VL in cats (Maia and Campino 2011, Vides JP et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Cats and a different species of opossum ( M. domestica ) did not support sand fly development at all, and dogs were intermediate in their abilities to efficiently support the sand fly life cycle. These observations raise hypotheses about animals that could serve as potential reservoir hosts for Leishmania species (Humberg et al 2012). Recent studies have found evidence of VL in cats (Maia and Campino 2011, Vides JP et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…In a similar study performed in Minas Gerais, five of 20 Didelphis marsupialis were PCR positive for Leishmania sp., and 24 out of 111 were positive by IFAT (Schallig et al 2007). L. infantum DNA was detected by PCR in 15 out of 54 Didelphis albiventris opossums in the State of Mato Grosso do Sul, Brazil (Humberg et al 2012). Leishmania sp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the presence of opossum (Didelphis marsupialis) was an important risk factor for the transmission of leishmaniasis, since opossum populations usually have high infection rates in urban endemic area, suggesting that this species may act as a natural link between domestic and sylvatic Leishmania life cycles, especially because opossums and dogs can inhabit the same environment [37,38]. Moreover, opossum infection by L. infantum chagasi has been associated with human VL in some areas [36].…”
Section: Discussionmentioning
confidence: 99%
“…The search for leishmaniasis in opossum is justified by reports of natural infection of this animal in different regions of Brazil [12,35,36]. Previous studies showed that the presence of opossum (Didelphis marsupialis) was an important risk factor for the transmission of leishmaniasis, since opossum populations usually have high infection rates in urban endemic area, suggesting that this species may act as a natural link between domestic and sylvatic Leishmania life cycles, especially because opossums and dogs can inhabit the same environment [37,38].…”
Section: Discussionmentioning
confidence: 99%